2018
DOI: 10.1002/ecs2.2524
|View full text |Cite
|
Sign up to set email alerts
|

Exploring variation in phyllosphere microbial communities across four hemlock species

Abstract: The hemlock woolly adelgid (HWA) is an insect native to Asia and likely western North America. First reported in eastern North America in 1951, it has devastated eastern hemlock (Tsuga canadensis) populations. Loss of hemlock will greatly affect the structure and function of eastern forests. Susceptibility to adelgid infestation varies within eastern hemlocks and across other hemlock species. Our study was conducted to determine whether eastern hemlocks share a similar stem (phyllosphere) microbial community w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
3
12
1
Order By: Relevance
“…Because the relative dominance of mycorrhizal types can potentially affect ecosystem-level processes (Phillips et al, 2013), the impact of HWA infestation on co-occurrence of AM and EM fungi in hemlock warrants detailed research. Consistent with earlier work (Rogers et al, 2018), we found a greater percent of the variation in the microbiome composition explained by host species than by HWA population level. The effect of host species on the microbiome composition was strongest in the needles, branches, and roots, where the plant has a relatively stronger control over the microbiome environment (Kembel et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Because the relative dominance of mycorrhizal types can potentially affect ecosystem-level processes (Phillips et al, 2013), the impact of HWA infestation on co-occurrence of AM and EM fungi in hemlock warrants detailed research. Consistent with earlier work (Rogers et al, 2018), we found a greater percent of the variation in the microbiome composition explained by host species than by HWA population level. The effect of host species on the microbiome composition was strongest in the needles, branches, and roots, where the plant has a relatively stronger control over the microbiome environment (Kembel et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…These broad taxonomic patterns among different plant-associated habitats resemble those found in other temperate tree species such as Magnolia kwangtungensis (Qian et al, 2019), Populus trichocarpa and P. deltoides × P. trichocarpa hybrids (Cregger et al, 2018), and Picea abies (Kovalchuk et al, 2018;Ren et al, 2019;Terhonen et al, 2019), suggesting that, at higher taxonomic levels, microbiomes are fairly consistent among tree species. However, as our study and others show, at more specific taxonomic levels, microbiomes diverge among closely related host species (Cregger et al, 2018;Rogers et al, 2018) and even among different genotypes of the same host species (Bálint et al, 2013;Veach et al, 2019).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations